Peningkatkan Kemampuan Berpikir Kreatif Peserta Didik melalui Strategi Peer Lesson Mata Pelajaran Matematika - Hidayati, Ika Septi; Sarumaha, Yenny Anggreini (Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2024)
This study aims to improve students' creative thinking skills through the Peer Lesson strategy in Mathematics learning for class VII students of MTs Darul Ulum Muhammadiyah Galur in the 2023/2024 academic year. This study uses a classroom action research method with two cycles. The subjects of this study were 14 class VII students at MTs Darul Ulum Muhammadiyah Galur, Kulon Progo Regency. The object of this study is critical thinking skills. Data were collected through test and non-test techniques, such as classroom observation and students interviews. The results of the study showed that the results of learning mathematics on the set material, class VII students who were taught using the active learning strategy of the peer lesson type were better than without using the active learning strategy of the peer lesson type at MTs Darul Ulum Muhammadiyah Galur. This is evidenced by the results in cycle 1 to cycle 2 increasing significantly.